Determination of metabolite differences between loquat nectar and honey by UPLC-MS/MS - Sun,Xin; Shu,Rui; Qu,Yuli; Dai,Junjun (PeerJ, 2025)
Honey is a widely consumed natural agricultural product. Honey bees produce honey by collecting nectar from different flowers and then metabolising it to form honey which is stored in the hive. The current focus of research has been on the primary characteristic metabolites of monofloral honey from different plant sources. There is a lack of understanding of the differences in the transformation and composition of overall metabolites between plant nectar and the honey that is processed by bees after nectar feeding. In this study, loquat nectar and mature loquat honey were used for the detection of all non-volatile metabolites in both by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Subsequently, an analysis was conducted on the primary metabolites, including saccharides, amino acids and their derivatives, nucleotides and their derivatives, lipids, and organic acids. In addition, the secondary metabolites, including flavonoids, phenolic acids, and terpenoid, were analysed. The results showed that there was a significant difference in the relative content of non-volatile metabolites between the two. We detected a total of 914 non-volatile metabolites, of which 834 were detected in loquat nectar and 759 in loquat honey. We analyzed the relative content of metabolites based on their classification and found that the relative content of primary and secondary metabolites showed different trends after processing by bees. Among them, the content of nucleotides and their derivatives and sugar metabolites in loquat honey was generally higher than that in loquat honey. This result presents a comprehensive picture of the non-volatile metabolite composition of loquat nectar and loquat honey, and systematically compares the changes in the relative content of the two substances.
Keywords: Honey; Nectar; Loquat; Phenolic acids; Flavonoids; UPLC-MS/MS; Eriobotrya japonica Lindl.